Gangguan Fungsi Sosial Anak Akibat Kekerasan Orang Tua: Studi Kasus Dikampung Perigi Bedahan Kota Depok - Gita Apliria; Muhammad Sahrul (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
Violence is usually carried out by someone against another person for a reason, for example because someone is very annoyed or angry with another person so that he commits violence intentionally or not. The research method used is descriptive qualitative. Data collection techniques are observation, interviews and documentation. The results of the research show that when violence begins, such as shouting and pinching children, this continues to include hitting and throwing things at children. Meanwhile, children who experience verbal violence such as verbal abuse or insults experience conditions related to feelings. Children will feel insecure, close themselves off, feel inferior and overthink